Optimization of Educational Television for Equity and Quality Improvement of Education in Indonesia - Ilham Marnola; Yulia Rahmi; Nurul Qomariyah Ahmad; Ali Umar; Siska Wahyuni (Edutechnium Journal of Educational Technology, 2025)
This paper provides an overview of Televisi Edukasi, a Television program and channel developed by the Ministry of Education and Culture to provide learning support. Televisi Edukasi has been active for a long time in Indonesia that can reach remote and outer areas with the help of satellite transmitters. Has content for educational and teaching activities as well as information about the policies of the Ministry of Education and Culture. Televisi Edukasi content can be used as content or learning material in the classroom, for the deepening of learning material either done in class with the subject teacher, studying at home under the guidance of the teacher or independent student learning. The government utilizes Televisi Edukasi to support learning that took place during the Covid Pandemic 19 period. With the help of Relay from TVRI, students can watch learning shows that have been made by Televisi Edukasi. However, efforts need to be made to increase the utilization of Televisi Edukasi programs both during the Pandemic and post-pandemic periods, as in fact there are still many limitations that occur so that education has not been optimally utilized in Indonesia both in structured learning activities and also in student independent learning activities.